(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The opening of circus schools in Brazil favored a range for learning circus knowledge and sheltered an interdisciplinary dimension of these practices, presenting itself as a proposal for the formation of new circus artists. To expand this dialogue, this article aims to reflect on the formation of the circus in Brazil and the pedagogical developments developed by Amercy Marrocos and Delisier Rethy, who worked as teachers in Brazilian circus schools, demonstrating that it was possible to train people born “off the canvas”. These masters turned upside down many values deposited to the presence of women in the circus universe and built narratives based on female references in the formation and pedagogy of circus knowledge, expanding the influence of circus arts in the Brazilian scene.